2003
DOI: 10.1590/s0104-42302003000400030
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência dos marcadores imunológicos Anti-GAD e Anti-IA2 em parentes de primeiro grau de diabéticos do tipo 1 em amostra da população da Grande São Paulo

Abstract: The prevalence of anti-GAD has been more prevalent among the PDMI. No differences were observed between prevalences for anti-IA2 showed by PDMI and controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
0
4
1
2
Order By: Relevance
“…It is known that GADA tend to be less frequent in Black African patients with T1D (23). On the other hand, previous Brazilian studies have found a similar prevalence of GADA positivity in Brazilian and Caucasian European T1D (5,24). Finally, we believe that the lack of patients with a very recent diagnosis (<12 months) could be a major factor explaining the low prevalence of GADA in our study population, especially in the group with a shorter duration of the disease.…”
Section: Discussioncontrasting
confidence: 40%
“…It is known that GADA tend to be less frequent in Black African patients with T1D (23). On the other hand, previous Brazilian studies have found a similar prevalence of GADA positivity in Brazilian and Caucasian European T1D (5,24). Finally, we believe that the lack of patients with a very recent diagnosis (<12 months) could be a major factor explaining the low prevalence of GADA in our study population, especially in the group with a shorter duration of the disease.…”
Section: Discussioncontrasting
confidence: 40%
“…We must highlight, however, that all of these positive results were of a low titer (below 10 U/L), but still well above the analytical and functional sensitivities of the technique (0.18 and 4 U/L, respectively) 19. In the control group of a study of beta-cell autoimmunity among children with thyroiditis, the prevalence of GADA was 3.8%,20 while in first-degree relatives of patients with DM1 the prevalence has been 10.1% 21. Higher prevalence of GADA in nondiabetic adults (40.4%) have only been reported among workers exposed to polychlorinated biphenyl products 22.…”
Section: Discussionmentioning
confidence: 98%
“…TPOA were measured by an immunofluorometric assay (autoDelfia, Turku, Finland) and we considered the reference value <52 U/mL for the population studied. Glutamic acid decarboxylase 65 (GADA) and Insulinoma antigen-2 (IA2A) antibodies were measured by a radioimmunoassay (RSR Ltd, Cardiff, UK) and according to previous study of our group we considered the reference value <1.72 and 0.97 U/mL respectively [ 28 ]. Fasting serum C-peptide (FCP) was measured using an immunofluorometric assay (autoDelfia, Turku, Finland) with detection limit of 0.015 ng/mL.…”
Section: Methodsmentioning
confidence: 99%